2020
DOI: 10.1093/jme/tjaa139
|View full text |Cite
|
Sign up to set email alerts
|

Cold Nights, City Lights: Artificial Light at Night Reduces Photoperiodically Induced Diapause in Urban and Rural Populations ofAedes albopictus(Diptera: Culicidae)

Abstract: Abstract As the planet becomes increasingly urbanized, it is imperative that we understand the ecological and evolutionary consequences of urbanization on species. One common attribute of urbanization that differs from rural areas is the prevalence of artificial light at night (ALAN). For many species, light is one of the most important and reliable environmental cues, largely governing the timing of daily and seasonal activity patterns. Recently, it has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 57 publications
0
22
0
1
Order By: Relevance
“…rural mosquito demes responded similarly (20). In moths, ALAN can disrupt larval development and pupal diapause (e.g., ref.…”
Section: Significancementioning
confidence: 94%
“…rural mosquito demes responded similarly (20). In moths, ALAN can disrupt larval development and pupal diapause (e.g., ref.…”
Section: Significancementioning
confidence: 94%
“…The fly population at the urban OCU site was exposed to light at 0.1 lux or higher during the night but was still able to enter diapause in the autumn in 2 years of the experimental period. Westby & Medley [ 43 ] also found that in a mosquito , populations in urban sites are still able to enter diapause in the autumn [ 43 ]. This may be related to an ability to minimize the effect of light at night at lower temperatures, as observed in our laboratory experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, such a strong effect on seasonality has been assumed conceptually [13,66] but has been poorly tested empirically. Furthermore, most of the studies in this context used 'simulated' artificial light at night to investigate its effect on seasonality [26,30,31,43,44,[67][68][69]. Field studies with 'natural' artificial light at night are awaited [70,71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…albopictus . In urban field sites, although populations showed differences in diapause induction in early September, later on, all populations reached high levels of diapause, suggesting that the effect of artificial light may be minimized due to vegetation or other factors ( Westby and Medley 2020 ).…”
Section: Human-mediated Environmental Influences On Vectorial Capacity and Behaviormentioning
confidence: 99%